2012
DOI: 10.1016/j.cell.2012.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Step-Wise Methylation of Histone H3K9 Positions Heterochromatin at the Nuclear Periphery

Abstract: The factors that sequester transcriptionally repressed heterochromatin at the nuclear periphery are currently unknown. In a genome-wide RNAi screen, we found that depletion of S-adenosylmethionine (SAM) synthetase reduces histone methylation globally and causes derepression and release of heterochromatin from the nuclear periphery in Caenorhabditis elegans embryos. Analysis of histone methyltransferases (HMTs) showed that elimination of two HMTs, MET-2 and SET-25, mimics the loss of SAM synthetase, abrogating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
756
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(822 citation statements)
references
References 55 publications
59
756
5
2
Order By: Relevance
“…Conversion of H3K9me2 to H3K9me3 is most likely mediated by the joint action of Cbr-MES-2 and Cbr-SET-25, and perhaps additional histone methyltransferases (Figure 4). While MES-2 is important for generation of H3K9me3 in the C. elegans germ line (Bessler et al 2010), SET-25 has been shown to be important for acquisition of H3K9me3 in the C. elegans embryo (Towbin et al 2012). We found that RNAi inactivation of SET-25 in C. elegans results in accumulation of H3K9me2 in the germ line ( Figure S4), indicating Cel-SET-25 also functions in the germ line as suggested by Ashe et al (2012).…”
Section: H3k9me2 Vs H3k9me3mentioning
confidence: 62%
See 1 more Smart Citation
“…Conversion of H3K9me2 to H3K9me3 is most likely mediated by the joint action of Cbr-MES-2 and Cbr-SET-25, and perhaps additional histone methyltransferases (Figure 4). While MES-2 is important for generation of H3K9me3 in the C. elegans germ line (Bessler et al 2010), SET-25 has been shown to be important for acquisition of H3K9me3 in the C. elegans embryo (Towbin et al 2012). We found that RNAi inactivation of SET-25 in C. elegans results in accumulation of H3K9me2 in the germ line ( Figure S4), indicating Cel-SET-25 also functions in the germ line as suggested by Ashe et al (2012).…”
Section: H3k9me2 Vs H3k9me3mentioning
confidence: 62%
“…To distinguish between these possibilities, we depleted the methyltransferases Cbr-MES-2 and Cbr-SET-25, which mediate the conversion of H3K9me2 to H3K9me3 in C. elegans germ cells and embryos, respectively (Bessler et al 2010;Towbin et al 2012). Furthermore, inactivation of Cel-set-25 by RNAi revealed elevated levels of germ-line H3K9me2, indicating that SET-25 also functions in the C. elegans germ line to convert H3K9me2 to H3K9me3 ( Figure S4A).…”
Section: The X Chromosome Of Males Is Enriched For Different Repressimentioning
confidence: 99%
“…We therefore tested whether predicted H3K9 histone methyltransferases (HMTases) and potential interactors of HPL-2 also play a role in the ER stress response. Two HMTases, SET-25 and MET-2, are required for H3K9me in C. elegans (25,26). Whereas animals lacking set-25 showed a wild-type response to ER stress, animals lacking met-2 showed enhanced resistance (Fig.…”
Section: Hpl-2 Acts In the Same Pathway As The Rb Homolog Lin-35 And Thementioning
confidence: 99%
“…LADs have initially been discovered by DamID (DNA adenine methyltransferase [Dam] identification, a proximity assay). 2 Features of LADs include residence in overall transcriptionally silent heterochromatin 2,9 consistent with enrichment of this compartment at the nuclear periphery, 5,10,11 and a gene-poor content. 2 Large chromatin domains with similar properties have also been identified by chromatin immunoprecipitation (ChIP) of lamin A/C (referred to here as LMNA) or lamin B1 (LMNB1) coupled to array hybridization 12 or highthroughput sequencing (ChIP-seq).…”
Section: Introductionmentioning
confidence: 99%